DETERMINAN PUBLIKASI LAPORAN KEUANGAN PEMERINTAH DAERAH MELALUI INTERNET - Mya Dewi Trisnawati; Komarudin Achmad (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to examine and provide empirical evidence about the effects of political competition, local government size, leverage, local government wealth, local government type, and audit opinion on publication of local government financial statements through the internet. The population of this research  are local governments in Indonesia in 2012.  This  research used  210 local governments in Indonesia chosen by using purposive sampling method.  The result of this research shows that political competition, local government size, leverage, and local government wealth have significant influence toward publication of local government financial statements through the internet. This research failed to prove the influence of local government type and audit opinion on publication of local government financial statements through the internet. Internet programs into the village make increased use of the internet in the district. This caused local government of the city and district not different  to publish financial statements through the internet. Unqualified opinion  does not necessarily  indicate  the good signal of  local government financial management. Meanwhile, other audit opinion does not directly  indicate that  the signal of local government financial management is bad. Keywords:  publication of financial statements through the internet, local government, political competition, size, leverage, wealth, type, audit opinion.